Tìm x, biết:
a) | x | − 3 4 = 5 3
b) x − 3 2 = 1
Bài 4. Tìm số nguyên x , biết:
a) |x - 2|= 0 b) |x + 3|= 1 c) -3 |4 - x|= -9 d) |2x + 1|= -2
Bài 5. Tìm số nguyên x, biết:
a) (x + 3)mũ 2 = 36 b) (x + 5)mũ 2 =100 c) (2x - 4)mũ 2 = 0 d) (x - 1)mũ 3 = 27
bài 2:tìm x, biết:
a. x + 1^3 = 2^5 - ( -1^3 )
b. 3^7 - x = 1^4 - ( -3^5 )
a) \(x+1^3=2^5-\left(-1^3\right)\)
\(\Rightarrow x+1=33\)
=> x = 32
b) \(3^7-x=1^4-\left(-3^5\right)\)
\(\Rightarrow2187-x=1+243=244\)
=> x = 1943
a) \(\Leftrightarrow x+1=32+1\)
\(\Leftrightarrow x=32\)
Vậy x = 32
b) \(\Leftrightarrow2187-x=1+243\)
\(\Leftrightarrow2187-x=244\)
\(\Leftrightarrow x=1943\)
Vậy x = 1943
a) \(x+1^3=2^5-\left(-1^3\right)\)
\(x+1=32-\left(-1\right)\)
\(x+1=33\)
\(x=33-1\)
\(x=32\)
b) \(3^7-x=1^4-\left(-3^5\right)\)
\(2187-x=1-\left(-243\right)\)
\(2187-x=244\)
\(x=2187-244\)
\(x=1943\)
Tìm x, biết:a,x/4/2=4/x/2;b,x^4=y^4;x^5=y^5;(x+5)^3=-64;e,(2x-3)^2=9
1. Tìm số nguyên x, y biết:
a) \(^{3^{4-x}}=27\)
b) \(^{3^{-1}}.^{4^x}+3.^{4^x}=\dfrac{5}{3}.^{2^7}\)
Tìm x, biết:
a) \(\dfrac{x}{3}\) - 5 = \(\dfrac{2x}{5}\)
b) 4 + 3x = 8 - x
c) 2 . 3\(^{x+1}\) - 5 . 3\(^x\) = 243
a: =>1/3x-2/5x=5
=>-1/15x=5
=>x=-75
b: =>4x=4
=>x=1
c: =>6*3^x-5*3^x=243
=>3^x=243
=>x=5
Tìm x biết:
a) \(x:1\frac{2}{7} = - 3,5\)
b) \(0,4.x - \frac{1}{5}.x = \frac{3}{4}\)
a) \(1\frac{2}{7} = 1 + \frac{2}{7} = \frac{9}{2}\)
\(\begin{array}{l}x:1\frac{2}{7} = - 3,5\\x:\frac{9}{7} = - \frac{7}{2}\\x = - \frac{7}{2}.\frac{9}{7}\\x = - \frac{9}{2}\end{array}\)
b) \(0,4.x - \frac{1}{5}.x = \frac{3}{4}\)
\(\begin{array}{l}\frac{2}{5}.x - \frac{1}{5}.x = \frac{3}{4}\\\left( {\frac{2}{5} - \frac{1}{5}} \right).x = \frac{3}{4}\\\frac{1}{5}.x = \frac{3}{4}\\x = \frac{3}{4}:\frac{1}{5}\\x = \frac{3}{4}.5\\x = \frac{{15}}{4}\end{array}\)
Tìm x, biết:
a) \(\dfrac{4}{7}.x-\dfrac{2}{3}=\dfrac{1}{5};\)
b) \(\dfrac{4}{5}+\dfrac{5}{7}:x=\dfrac{1}{6}.\)
Lời giải:
a)
$\frac{4}{7}x=\frac{2}{3}+\frac{1}{5}=\frac{13}{15}$
$x=\frac{13}{15}:\frac{4}{7}=\frac{91}{60}$
b)
$\frac{5}{7}:x=\frac{1}{6}-\frac{4}{5}$
$\frac{5}{7}:x=\frac{-19}{30}$
$x=\frac{5}{7}:\frac{-19}{30}=\frac{-150}{133}$
a) \(\dfrac{4}{7}.x-\dfrac{2}{3}=\dfrac{1}{5}\)
\(\dfrac{4}{7}.x=\dfrac{1}{5}+\dfrac{2}{3}\)
\(\dfrac{4}{7}.x=\dfrac{13}{15}\)
\(x=\dfrac{13}{15}:\dfrac{4}{7}\)
\(x=\dfrac{91}{60}\)
b) \(\dfrac{4}{5}+\dfrac{5}{7}:x=\dfrac{1}{6}\)
\(\dfrac{5}{7}:x=\dfrac{1}{6}-\dfrac{4}{5}\)
\(\dfrac{5}{7}:x=\dfrac{-19}{30}\)
\(x=\dfrac{5}{7}:\dfrac{-19}{30}\)
\(x=\dfrac{-150}{133}\)
tìm số nguyên x,y,z biết:
a)3/x-5=5/x+1
b)3/x-5=-4/x+2
a: =>3x+3=5x-25
=>-2x=-28
hay x=14
b: =>3x+6=-4x+20
=>7x=14
hay x=2
a)
\(x+\left(x+2\right)+\left(x+4\right)+...+\left(x+98\right)=0\)
\(x+x+2+x+4+...+x+98=0\)
\(50x+\left(98+2\right).\left[\left(98-2\right):2+1\right]:2=0\)
\(50x+100.49:2=0\)
\(50x+49.50=0\)
\(50x=0-49.50\)
\(50x=-2450\)
\(x=-2450:50\)
\(x=-49\)
b)
\(\left(x-5\right)+\left(x-4\right)+\left(x-3\right)+...+\left(x+11\right)+\left(x+12\right)=99\)
\(x+x+x+...+x-5-4-3-...+11+12=99\)
\(18x+6+7\text{+ 8 + 9 + 10 + 11 + 12 = 99}\)
\(18x+63=99\)
\(18x=99-63\)
\(18x=36\)
\(x=36:18\)
\(x=2\)
a) x + (x + 2) + (x + 4) + ... + (x + 98) = 0
x + x + 2 + x + 4 + ... + x + 98 = 0
50x + (98 + 2).[(98 - 2) : 2 + 1]:2 = 0
50x + 100 .49 : 2 = 0
50x + 49.50 = 0
50x = 0 - 49.50
50x = -2450
x = -2450 : 50
x = -49
b) (x - 5) + (x - 4) + (x - 3) + ... + (x + 11) + (x + 12) = 99
x + x + x + ... + x - 5 - 4 - 3 - ... + 11 + 12 = 99
18x + 6 + 7 + 8 + 9 + 10 + 11 + 12 = 99
18x + 63 = 99
18x = 99 - 63
18x = 36
x = 36 : 18
x = 2
Tìm x, biết:
a) \(x-\dfrac{5}{6}=\dfrac{1}{2};\)
b) \(\dfrac{-3}{4}-x=\dfrac{-7}{12}.\)
\(a.\)
\(x-\dfrac{5}{6}=\dfrac{1}{2}\)
\(\Leftrightarrow x=\dfrac{1}{2}+\dfrac{5}{6}=\dfrac{3+5}{6}=\dfrac{8}{6}=\dfrac{4}{3}\)
\(b.\)
\(-\dfrac{3}{4}-x=-\dfrac{7}{12}\)
\(\Leftrightarrow x=-\dfrac{3}{4}--\dfrac{7}{12}=-\dfrac{3}{4}+\dfrac{7}{12}=\dfrac{\left(-3\right)\cdot3+7}{12}=\dfrac{-2}{12}=-\dfrac{1}{6}\)
a)x=1/2+5/6
x=/3/6+5/6
x=8/6=4/3
b)x=-3/4- (-7/12)
x=-9/12-(-7/12)
x=-1/6
a) \(x-\dfrac{5}{6}=\dfrac{1}{2}\)
\(x=\dfrac{1}{2}+\dfrac{5}{6}\)
\(x=\dfrac{4}{3}\)
b) \(\dfrac{-3}{4}-x=\dfrac{-7}{12}\)
\(x=\dfrac{-3}{4}-\dfrac{-7}{12}\)
\(x=\dfrac{-1}{6}\)